Sustainability and corporate environmental management - Elkington, John (Henry Stewart Talks, 2011)
How the sustainability agenda evolved, Origination of the Triple Bottom Line, 4 societal pressure waves, Sustainability 1.0, 2.0 and 3.0, Social enterprise, Volans book, The Power of Unreasonable People, and the challenge of replication and scaling, Volans study, The Phoenix Economy and the Volans 5-stage scaling model, Volans study, The Transparent Economy and the TIGERS agenda, Traceability, Integrated reporting, Government frameworks and incentives, Environmental boundaries, Ranking & rating schemes, Shadow economies, Divide between urgency of key sustainability challenges and the effectiveness of companies in tackling them, World Business Council for Sustainable Development study, Vision 2050